2021
DOI: 10.1186/s12877-021-02597-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional decline in hospitalized older patients with coronavirus disease 2019: a retrospective cohort study

Abstract: Background This study aimed to determine the frequency of functional decline and to identify the factors related to a greater risk of functional decline among hospitalized older patients with coronavirus disease 2019 (COVID-19). Methods We reviewed the medical records of patients aged over 65 years who were admitted to a tertiary care hospital for COVID-19 over 1 year from February 2020. We evaluated the proportion of functional decline, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
(30 reference statements)
4
18
0
3
Order By: Relevance
“…In our study, 36% of patients lost at least 1 point on Katz ADL, which is consistent with published studies. Indeed, functional decline after COVID-19 was estimated between 27 and 54% in older patients [ 13 , 14 ]. This occurrence varies greatly among studies populations and according time to assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 36% of patients lost at least 1 point on Katz ADL, which is consistent with published studies. Indeed, functional decline after COVID-19 was estimated between 27 and 54% in older patients [ 13 , 14 ]. This occurrence varies greatly among studies populations and according time to assessment.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in the methods part, the sample size calculation (SSC) was not possible when we started the study. The SSC varies between to 317 patients to include (considering a 80% target power, a 2-sided alpha of 0.05, a 30% COVID-19 mortality rate in acute geriatric ward and pejorative 10% follow-up withdrawal) as new data details post-COVID functional decline between 30 to 50% depending on the time of assessment and the settings of recent published studies [ 13 , 14 ]. Third, there is an important missing data for long-terms symptoms and frailty transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Barthel index has been used as an important indicator of hospital outcome [ 25 ] and could be used as a predictor of mortality [ 26 ]. On the other hand, there have been studies on patients with COVID-19 that aimed to identify predictive factors of functional prognosis [ 18 , 27 , 28 ]. Similar to our study, Hosoda et al also discovered that baseline activities of daily living impairment was associated with a greater risk of functional decline at discharge [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this study is to find out whether a COVID-19 patient’s physical performance along with other laboratory data upon admission are associated with both functional prognosis and hospitalization stay duration. Based on a past study [ 18 ], which showed impaired baseline activities of daily living being associated with functional decline at discharge, we hypothesize that COVID-19 patients with a poor physical performance upon admission shall have longer hospital stays and worse functional outcomes.…”
Section: Introductionmentioning
confidence: 99%